2019
DOI: 10.3390/nu11010203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of a Growing up Milk Lite vs. Cow’s Milk on Diet Quality and Dietary Intakes in Early Childhood: The Growing up Milk Lite (GUMLi) Randomised Controlled Trial

Abstract: Summary scores provide an alternative approach to measuring dietary quality. The Growing Up Milk-Lite (GUMLi) Trial was a multi-centre, double-blinded, randomised controlled trial of children randomised to receive a reduced protein GUM (GUMLi) or unfortified cow’s milk (CM). In a secondary analysis of the GUMLi Trial, we used the Probability of Adequate Nutrient Intake (PANDiet) to determine the nutritional adequacy of the diets of participating children living in Auckland. The PANDiet was adapted to the New Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
4
15
0
5
Order By: Relevance
“…In accordance with previous studies [4,7,53], a high intake of SFAs was observed in the Spanish pediatric population, with both cohorts showing a high median intake of SFAs (12.87% of TCV in SRS and 12.08% in AMS). The majority of children above the recommended amount of <8%E of SFAs established by the UN-FAO; nevertheless, the AMS cohort had a lower percentage of children above and a higher percentage meeting the recommendations than the SRS cohort.…”
Section: Lipid Profile and Adequacysupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies [4,7,53], a high intake of SFAs was observed in the Spanish pediatric population, with both cohorts showing a high median intake of SFAs (12.87% of TCV in SRS and 12.08% in AMS). The majority of children above the recommended amount of <8%E of SFAs established by the UN-FAO; nevertheless, the AMS cohort had a lower percentage of children above and a higher percentage meeting the recommendations than the SRS cohort.…”
Section: Lipid Profile and Adequacysupporting
confidence: 92%
“…Eussen et al [69] showed that for infants and young children 12 to 18 years old in the UK Diet and Nutrition Survey, replacing habitual cow's milk intake by an equal volume of 300 mL of adapted milk led to nutritional intake more in line with recommendations. Besides, Lovell [53], in a multi-center, double-blinded, randomized controlled trial of children receiving reduced-protein growing-up milk (GUMLi) or unfortified CM, assessed the probability of adequate nutrient intake (PANDiet) at months 7, 8, 10, and 11 post-randomization, showing that total PANDiet scores were significantly higher in the GUMLi group, indicating better diet quality.…”
Section: Contributions Of Food Groups To Fat and Major Fatty Acid Conmentioning
confidence: 99%
“…Therefore, in a recent position paper, the Committee considered it of interest to determine whether YCF intake could correct (and to what extent) some of these deficits, as compared to CM. A few months later, the results of a study conducted in New Zealand and Australia asserted that the consumption of YCF was associated with increased likelihood of meeting nutrient requirements [8]. Owing to the small number of studies conducted to date, it made sense to assess the nutritional intake of YCF-consuming children in Europe, using the data from the Nutri-Bébé study.…”
Section: Introductionmentioning
confidence: 99%
“…Em outros países, ele costuma ser vendido como leite fortificado, e não composto lácteo, 11 mas apresenta uma lista longa de ingredientes e não está caracterizado nominalmente na legislação, assim como ocorre no Brasil. Poucos estudos mostram a necessidade de utilização desse produto, [12][13][14] já que existem outros que podem suprir necessidades em casos especiais, como desnutrição e erros inatos do metabolismo. A questão é que não há definição legal internacional a respeito de sua regulamentação.…”
Section: Introductionunclassified